Indigenization of pre-service English language education a program development using Print's model - Paguirigan, Joel Amilhasan M., Jr (College of Education, University of the Philippines Diliman, 2015)
Curriculum programs provided to preservice teachers determine the quality of a nation's education. To meet the varied demands of learners, curriculum programs for prospective teachers should be engineered to develop their competence in meeting the learners' needs, which may emanate from students' diversity in race, social class, or religion, that pose a huge challenge requiring teachers to create learning environments that recognize every student's cultural identity if each learner's academic success has to remain the ultimate thrust of schooling. If teachers are to address diversity in classrooms where an increasing number of diverse students swarm in year after year, it is essential that they are educated to gain competency in indigenizing their instruction so that an inclusive classroom, learner-centered teaching, and empowering learning environment is afforded to a class that is culturally and linguistically diverse. Teacher's qualification should then be based on a systematic framework that equips teachers to acquire the knowledge, skills, attitudes, and dispositions necessary to meet the diverse needs of learners. Indigenization of the English curriculum has been posited to be an essential step for students to become highly proficient in English. However, an innovative program has to be designed in order for this plan to be concretized. Using documentary analysis as its primary technique of data collection, this qualitative study delved on proposing a program development to indigenize English language teaching (ELT) by identifying gaps in the existing program for the education and training of prospective secondary English teachers in the Philippines. Analysis of the program standards for the BSEd English majors as stated in the Commission on Higher Education (CHED) guidelines as well as investigation of the learning intent stated in each of the course syllabi of the ten (10) TEIs included in this research provided vital information for the proposed development of a program for the indigenization of English language teaching in Philippine secondary schools. Consequently, programs posited to close the identified gaps were proposed. Questions answered in this study include: 1) What are the competencies needed by English language teachers to be able to indigenize language teaching?; 2) How can these competencies be developed?; 3) What are the learning objectives to develop these competencies?; 4) What are the learning content to be included in the indigenized program?; 5) What learning activities are needed to achieve the learning objectives?; and 6) What evaluation/assessment tools should be used to determine whether learning intent has been achieved? This descriptive study was limited to the identification of the competencies that are or are not being addressed by the curricula prescribed by the Commission on Higher Education (CHED) and 10 TEIs in the Philippines on how to indigenize English language teaching. Analyses of the CHED program standards and the course objectives of each of the course subjects for the BSEd program were done against the list of identified competencies unique for indigenization from 17 frameworks culled from different theorists, organizations, and institutions around the world. This research designed to develop a program for the indigenization of English language teaching as its output involved three phases: standard setting, document analysis and curriculum mapping, and program development using Print's model of curriculum development. Two options were offered to develop the 14 competencies among the preservice English language teachers. A revised program should be implemented or applied for the preservice BSEd English majors in which the consolidated 14 competencies for indigenization are targeted to be developed through integration of content in the existing course subjects. The other option proposes courses to be added as essential components of the Professional Education courses.